Elevated Serum Levels of SCUBE1, a Marker for Coagulation, in Patients with Breast Cancer - Topcu, Turkan Ozturk; Kavgaci, Hall; Ozdemir, Feyyaz; Aksoy, Asude; Erdem, Dilek; Mentese, Ahmet; Aydin, Fazil (Tohoku Univ Medical Press, 2015)
Breast cancer (BC) is the most common cancer among women and a major cause of death. Signal Peptide-Cub-Epidermal growth factor domain-containing protein-1 (SCUBE1) is secreted under hypoxia and inflammatory conditions from platelet alpha granules. Its biological function is uncertain, although it may be a procoagulant substance in cancer patients. SCUBE1 is useful for identifying thrombotic diseases, including cancers and acute coronary syndromes. D-dimer reflects the relationship between coagulation activation and fibrinolysis; namely, thrombosis and D-dinner levels are closely linked. This is the first investigation of the potential diagnostic and prognostic value of SCUBE1 levels in patients with BC. Fifty patients and 33 age-matched and body mass index-matched healthy controls were enrolled. Blood samples were collected before chemotherapy regimens commenced. Serum SCUBE1 and D-dimer levels were measured before adjuvant chemotherapy and were compared to the healthy controls. SCUBE1 levels were determined using an enzyme-linked immunosorbent assay (ELISA) method. SCUBE1 and D-dimer levels were significantly higher in patients than in the controls (p = 0.03 and p < 0.001, respectively). A cut-off value of 1.55 ng/mL for SCUBE1 was associated with 62% sensitivity and 72.7% specificity and with positive predictive value of 77.5% and negative predictive value of 55.8%. Two patients with high SCUBE1 and D-dimer levels also developed pulmonary embolism. SCUBE1 may indicate hypercoagulability in patients with BC and thus help identify patients at greater risk of thrombosis and requiring anti-thrombosis treatment. SCUBE1 may also be used as an assistant test for identifying patients at risk of BC.
Keywords: breast cancer; cut-off value; D-dimer; SCUBE1; thrombosis